Ecological Functions of Polychaetes Along Estuarine Gradients - Martins, Amanda Domingues; Barros, Francisco (Frontiers in Marine Science, 2022)
Function in ecology can be understood as the role that each component plays in the surrounding environment. It can be studied through the functional traits of organisms and depends on variations of abundance in time and space. Nevertheless, traits should be clearly associated with functions. The functions performed by estuarine macrofauna along estuarine gradients and its variation in time are scarcely studied. We expected that the functional structure (i.e. the set of functions in a site) would not change significantly over estuarine gradients, even with changes in taxonomic composition, since different taxa may have similar traits, allowing the performance of the same functions. We used polychaete assemblages along three tropical estuaries sampled four different times, to test for differences in functional intensity between estuarine salinity zones (Venice system). From a literature search we selected the most frequent ecological functions performed by estuarine benthic assemblages and we explicitly established which polychaete functional traits, or combinations of traits, were directly related to these functions. Nutrient cycling, bioturbation and fragmentation of organic matter were the most frequent functions. We discovered that the last two were present throughout the entire salinity gradient (i.e. along different salinity zones) but with different intensities. The intensity of functions may also show significant variability in time. Nutrient cycling and fragmentation of organic matter showed strong variation among estuarine zones. Using traits explicitly associated with ecological functions is necessary to investigate function and function intensity. Future studies should investigate how precisely traits may alter specific environmental characteristics and ecosystem properties.